Conceptualization of Workplace Spirituality in an Eastern Context - Shrestha, Arjun Kumar; Luitel, Bal Chandra; Nandram, Sharda S.; Petchsawang, Pawinee (Journal of Business and Management Research, 2023)
Workplace spirituality is a complex construct and is perceived differently in different cultures and contexts. The purpose of this study was to construct the meaning of workplace spirituality from the perceptions of employees in an Eastern context, particularly Nepal, which is primarily dominated by the Vedic and Buddhist spiritual traditions. This study utilized the constructivist grounded theory methodology to elucidate the meaning of WPS. The analysis of data revealed that WPS is a multi-dimensional construct having nine distinct dimensions – Altruistic Motive, Interpersonal Positivity, Compassion, Inner Calmness, Duty Orientation, Sense of Collaboration, Interconnectedness, Self-Regulation, and Higher Consciousness. The emergence of these dimensions is discussed in light of the Western WPS literature and the teachings of Vedic and Buddhist spiritual traditions. Finally, practical and research implications are drawn and the study’s limitations are highlighted.